Virtual Reality and Augmented Reality Exergames for older fallers: considerations about design and applicability by physical therapists - Pereira, Guido Augusto Faria; Bacha, Jéssica Maria Ribeiro; Silva, Izaura Beatriz Araújo Novais; Kim, Da Hee Chun; Pompeu, José Eduardo; Lopes, Roseli de Deus (Anais Estendidos do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames), 2021)
This work investigates the application of virtual reality (VR) and augmented reality (AR) exergames for older fallers, through a literature review and an exploratory technological research. We developed an exergame called BALLOONS to understand the main design concerns and to be able to evaluate the applicability based on physical therapists evaluation. Three different immersive systems running the same game BALLONS were implemented, two as VR exergames and one as an AR exergame. Test and evaluation sessions were conducted with eleven physiotherapists. The results point to a positive evaluation by experts in terms of safety, tolerability, and acceptability. The findings also suggest the need for technical improvements, such as the development of lighter and more comfortable headsets, to increase acceptability and the need of a larger variety of cognitive activities and frequency adjustments of physical exercise, to increase applicability and value for rehabilitation.